Hukum kebijakan ekonomi : pancasila dan eksistem kerakyatan dalam menghadapi kapitalisme glombang di indonesia - Maulina, Anisa Turrohmatul (Maliki Interdisciplinary Journal, 2025)
This study examines how Indonesia applies Pancasila principles in its economic strategy in facing global capitalism. The Indonesian government responded to increasing international concerns, such as the financial crisis, by issuing a Government Regulation in the form of a Law (Perppu) as a short-term legal basis for an emergency economic strategy. This article emphasizes the contribution of Pancasila in maintaining the nation's economic independence and the people's economy. In contrast to the capitalist paradigm which prioritizes individual profits, Pancasila is the basis for developing fair and sustainable policies. In addition, this study highlights the importance of MSMEs and cooperatives in strengthening the local economy and the need for policies that encourage community economic growth in the face of international competition